- #1

Sucvicbil

- 4

- 0

**TL;DR Summary:**Isolating coefficient contribution to outcome change

This is a problem I've been trying to solve for almost 3 days now, without any solutions.

Say we have x + y + z = 5, and x is 1, y is 1, and z is 3. We have a second equation = 2x + 3y + 4z = 17. Using the outcome difference based on the coefficient change alone observed between the first and second equation, how can we predict the outcome of a new equation = 6x + 5y + 7z = ? without using the values of x, y or z at all. Seems deceptively simple at first, but it seems unsolvable.